As concepções de leitura de crianças e sua relação com o letramento: estudo de caso em uma escola pública de Fortaleza - Almeida, Larissa Naiara Souza de (2016)
This research aimed to investigate the children reading conceptions of the 3rd year of elementary school to a public school in Fortaleza and its relation to literacy. The theoretical principles underlying this research are guided by the sociointeractionist approach of Vygotsky. The research, qualitative, nature is characterized as a case study and developed in a public institution of elementary school in the city of Fortaleza. Participated in twelve children research in the range of eight to twelve years old. The study was conducted in four stages, namely 1. exploratory research for the choice of field of study; 2. pilot study; 3. application of design-story instrument and semi-structured interviews; 4. application range of reading practices in everyday life of children. To collect the data we used drawing-story, semi-structured interview and a range of reading practices in everyday life of children. It was found that children understand reading very diverse and widely. They identified reading conceptions ruled on the domain of a technique for the practice of fluent reading. In contrast, other concepts identified by the children reading tied to an activity that involved in understanding and attribution of meaning. They also identified reading concepts related to pleasure, entertainment, imagination, knowledge, among others. As for the reading practices in everyday life and school, it was found that the children used diverse practices relating them to these two contexts. After analyzing the data, it was concluded that the reading conceptions presented by the children foster reading comprehension as a social knowledge. They include reading as an act that should be used in social contexts as their own interests, suggesting a reading relationship with the literacy perspective. It also appears from that for children reading practices should be carried out according to their needs and interests.